2020
DOI: 10.3389/fcell.2020.598620
|View full text |Cite
|
Sign up to set email alerts
|

Safrana l Prevents Prostate Cancer Recurrence by Blocking the Re-activation of Quiescent Cancer Cells via Downregulation of S-Phase Kinase-Associated Protein 2

Abstract: The re-proliferation of quiescent cancer cells is considered to be the primary contributor to prostate cancer (Pca) recurrence and progression. In this study, we investigated the inhibitory effect of safranal, a monoterpene aldehyde isolated from Crocus sativus (saffron), on the re-proliferation of quiescent Pca cells in vitro and in vivo. The results showed that safranal efficiently blocked the re-activation of quiescent Pca cells by downregulating the G0/G1 cell cycle regulatory proteins CDK2, CDK4, CDK6, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Although the E2Fs pathway is often deregulated in cancer, the roles of E2F1 as a proliferation or cell death promoter in tumorigenesis are still far from being understood [ 33 , 34 ]. Numerous studies indicate that E2F1 transcription factor is one of the most in-depth E2Fs family members in tumor research, and the high expression of E2F1 is of great significance for the poor prognosis of malignant tumors such as gastric cancer [ 35 ], hepatocellular carcinoma [ 36 ], pancreatic cancer [ 37 ], and prostate cancer [ 38 ]. Ma et al [ 9 ] have first reported that the mRNA level of E2F1 in renal clear cell carcinoma tissue is related to tumor pathological parameters, including diameter, Fuhrman tumor grade, pT staging, TNM staging and macrovascular infiltration (MAVI), and E2F1 expression with the increase of tumor tissue grade; they also found that E2F1 has promoting effects on the proliferation, migration, and invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the E2Fs pathway is often deregulated in cancer, the roles of E2F1 as a proliferation or cell death promoter in tumorigenesis are still far from being understood [ 33 , 34 ]. Numerous studies indicate that E2F1 transcription factor is one of the most in-depth E2Fs family members in tumor research, and the high expression of E2F1 is of great significance for the poor prognosis of malignant tumors such as gastric cancer [ 35 ], hepatocellular carcinoma [ 36 ], pancreatic cancer [ 37 ], and prostate cancer [ 38 ]. Ma et al [ 9 ] have first reported that the mRNA level of E2F1 in renal clear cell carcinoma tissue is related to tumor pathological parameters, including diameter, Fuhrman tumor grade, pT staging, TNM staging and macrovascular infiltration (MAVI), and E2F1 expression with the increase of tumor tissue grade; they also found that E2F1 has promoting effects on the proliferation, migration, and invasion of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that E2F1 can play various roles in different cancers ( 28 ). It has recently been reported that safranal inhibits cell cycle re-entry of quiescent PCa cells by deregulating the transcriptional activity of E2F1 ( 29 ). Hagiwara et al indicated that through the integration of E2F1 and esBAF, MUC1-C facilitates the progression of neuroendocrine PCa ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study has revealed that Safranal stunts the tumour growth of quiescent prostate cancer cell xenografts; depletes SKP2, E2F1, NF-κB p65, p-IkBa (Ser32), c-MYC, p-Rb (Ser807), CDK4, CDK6, and CDK2; and causes accumulation of p27 and p21 proteins. This preclinical evidence indicates that by targeting the NF-κB/E2F1-SKP2 axis, safranal can counteract cancer recurrence and progression [25].…”
Section: Safranalmentioning
confidence: 96%